PENGEMBANGAN UNIT USAHA INDUSTRI KECIL MELALUI METODE PEMETAAN DAN â€œNEED ASSESSMENTâ€ - Fafurida, F; Nihayah, Dyah Maya (Universitas Negeri Semarang, 2012)
Mapping industry and need assessement are the first steps for developing the industrial sector. This study aims to describe the performance of the industry, prepare the map of industrial development potency and identify the need assessement on industries in Sub Gunungpati. The data was obtained from the survey by spreading questionnaires and Focus Group Discussion (FGD). The descriptive statistical analysis is used in this study. The result shows that there are 12 types of industries in the Village Gunungpati. However, most of these industries do not have a good management of the business eventhough they have been running their industries for a long time. It can be seen from several aspects, such as accounting and finance, production and marketing. Every type of industry has different condition and distribution. There is only one type of industry which form a large cluster; it is the industries that produce red bricks in Ngrembel. Finally, the result of need assessment shows that trainings on administrative records, financial report, innovation on production machines, packaging, marketing, obtaining raw materials, waste management are needed to increase the business capacity.Â Pemetaan industri dan need assessement merupakan langkah awal dalam pengembangan sektor industri. Penelitian ini bertujuan untuk menggambarkan performance industri, menyusun peta potensi pengembangan industri dan mengidentifikasi need assessement pada industri-industri di Kelurahan Gunungpati. Data diperoleh dari metode survey dengan kuisioner dan Focus Group Discussion (FGD). Analisis yang dilakukan adalah analisis deskriptif statistik. Hasil penelitian menunjukkan ada 12 jenis industri di Kelurahan Gunungpati. Meski sudah berdiri lama, mayoritas industri- industri tersebut belum memiliki manajemen pengelolaan usaha yang baik. Ini dapat dilihat dari beberapa aspek, antara lain aspek pembukuan dan keuangan, produksi dan pemasaran. Setiap jenis industri memiliki kondisi dan sebaran yang berbeda-beda. Hanya ada satu jenis industri yang membentuk cluster besar yaitu industri pembuatan bata merah di daerah Ngrembel. Hasil need assessment menunjukkan bahwa pelatihan pencatatan administrasi, pelatihan penulisan laporan keuangan, inovasi alat produksi, pelatihan teknik pengemasan, pelatihan teknik pemasaran, kemudahan memperoleh bahan baku, dan pengelolaan limbah produksi dibutuhkan untuk meningkatkan kapasitas usaha.Â